Козаки у шведському полоні в часи Великої Північної війни 1700–1721 рр.: значення біографічного аспекту. Частина друга - Філіпова, Г. (Сiверянський лiтопис, 2019)
Автором продовжено дослідження перебування вихідців з полків Гетьманської
держави (Стародубського, Прилуцького тощо) у шведському полоні протягом Великої
Північної війни 1700–1721 рр. Увага акцентується на біографічних відомостях, почерпнутих з архівних джерел. Автором здійснено спробу простежити як характерні
нюанси перебування козаків у Швеції та Німеччині, так і перипетії повернення додому,
адаптацію до життя після полону, сімейні обставини тощо. На нашу думку, розвиток
студіювання окресленої теми у межах біографістики дає змогу повніше окреслити
соціальну ситуацію в Гетьманській державі на початку XVIII ст. та виявити безліч
побутових подробиць, які допомагають сформувати повніший погляд на епоху. This article describes the cases of the Ukrainian Cossacks’ (mainly Starodub regiment)
stay of the in the Swedish captivity during the Great Northern War 1700–1721. The author
focuses on biographical data and coverage of everyday life characteristics of Cossacks far
from their homeland.
Archive files from 51th fund of the Central State Historical Archive of Ukraine have
become the source base for the research. These are hetman’s universals, petitions, materials
of court cases – in general, various documents that provide numerous details of the life of
the population of Hetman State in the early 18th century.
The article presents data on representatives of the Cossack elite and ordinary Cossacks, on
their attempts to return home, on their way back from Sweden to Ukraine, on social adaptation
after years of captivity and deprivation.
On the basis of this material, as well as data published in the previous author’s article on
the same topic, it is possible to draw a number of conclusions valuable for studying the events
of the Northern War in the territory of the Hetman regiments. Most of the Cossacks became
prisoners of war after the 1706 Lithuanian campaign; the conditions of their detention in
Stockholm and its environs, Szczecin, Königsberg and so on, were extremely difficult, and
the sums required for the ransom and the overcoming of the way back were considerable; for
this reason, representatives of the Cossack sergeant were redeemed; returning to the Hetman
State, most of the ex-prisoners of war discovered that their households were devastated.
We believe that further study of the presence of Ukrainian Cossacks in Swedish captivity
and the search for new sources on this issue is necessary for understanding the global social
processes that took place on the territory of Ukraine in the first quarter of the 18th century,
as well as intercultural dialogue during the Northern War.